Receiver functions using OBS data: Promises and limitations from numerical modelling and examples from the Cascadia Initiative - Audet, Pascal (Université d'Ottawa | University of Ottawa, 2016)
The expanding fleet of broad-band ocean-bottom seismograph (OBS) stations is facilitating the study of the structure and seismicity of oceanic plates at regional scales. For continental studies, an important tool to characterize continental crust and mantle structure is the analysis of teleseismic P receiver functions. In the oceans, however, receiver functions potentially suffer from several limiting factors that are unique to ocean sites and plate structures. In this study, we model receiver functions for a variety of oceanic lithospheric structures to investigate the possibilities and limitations of receiver functions using OBS data. Several potentially contaminating effects are examined, including pressure reverberations from the water column for various ocean-floor depths and the effects of a layer of low-velocity marine sediments. These modelling results indicate that receiver functions from OBS data are difficult to interpret in the presence of marine sediments, but shallow-water sites in subduction zone forearcs may be suitable for constraining various crustal elements around the locked megathrust fault. We propose using a complementary approach based on transfer function modelling combined with a grid search approach that bypasses receiver functions altogether and estimates model properties directly from minimally processed waveforms. Using real data examples from the Cascadia Initiative, we show how receiver and transfer functions can be used to infer seismic properties of the oceanic plate in both shallow (Cascadia forearc) and deep (Juan de Fuca Ridge) ocean settings.
Keywords: Time-series analysis; Body waves; Wave scattering and diffraction; Ocean-bottom Seismic data